Application of the FD-method to the solution of the Sturm-Liouville problem with coefficients of special form - Klymenko, Ya. V.; Makarov, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We use the functional-discrete method for the solution of the Strum-Liouville problem with coefficients of a special form and obtain the estimates of accuracy. The numerical experiment is performed by using the Maple-10 software package.